SUBTITLE ERROR TYPOLOGIES IN UNOFFICIAL MOVIE STREAMING WEBSITE BY USING FAR MODEL - Amilia, Ika Kartika; Hasni, Rizka Alvina (Annual International Conferences on Language, Literature, and Media, 2023)
This study was intended to investigate the types of errors in the movie subtitles available on a movie online streaming, LayarKaca21 (LK21). The research method applied is a descriptive case study. The data were collected by comparing the English version of the subtitles, the LK21’s version, and the Indonesian subtitles on Netflix. The movie taken as a data source was of the animation genre, entitled How to Train Your Dragon: The Hidden World . The data found were analyzed based on Pederson’s typology of subtitle errors, FAR Model standing for Functional Equivalence, Acceptability, and Readability. The errors were classified into distinct categories: functional equivalence errors, including semantic and stylistic discrepancies; acceptability errors encompassing grammatical, spelling, and idiomatic inaccuracies; and readability errors involving segmentation and spotting, reading speed and line length, and punctuation and graphics. Throughout the analysis, 716 errors were identified, comprising 316 functional equivalence, 105 acceptability, and 295 readability errors. The investigation outcomes unveiled that most errors within LK21 predominantly fell under the functional equivalence category. Such errors inherently possess the potential to significantly hinder viewers' comprehension of the conveyed messages in the movies or series they engage with. Given the central role of subtitles in facilitating audience understanding, the presence of functional equivalence errors within LK21's subtitles raises concerns about the quality and effectiveness of the platform's subtitles.